Pivoting to Respond to COVID-19: Lessons Learned from Health Initiatives of a Student-Run Clinic - Dana Button; Bin Chen; Huong Nguyen; Lisa Mah-Park; Alyssa Hjelvik; Rachel Lockard (Journal of Student-Run Clinics, 2022)
Bridges Collaborative Care Clinic (BCCC) is a student-led, nonprofit organization providing no-cost health and social services to chronically marginalized populations in Portland, Oregon. In response to physical distancing measures during the early stages of the coronavirus disease 2019 (COVID-19) pandemic, health professions programs across the country suspended in-person clinical activities for students. As a result, BCCC clinical operations were canceled for the foreseeable future. In response, student leaders and volunteers started four health initiatives including the following: 1) organizing a mask-making network to create homemade masks for local organizations in need; 2) forming a real-time capacity needs assessment for local safety net organizations for people with substance use disorders; 3) collaborating with a local Asian health services nonprofit to organize a multilingual volunteer and translator network to deliver food and health supplies to Vietnamese, Korean, Cantonese, and Mandarin speaking elders; and 4) organizing a virtual 5K run/walk fundraiser for an organization that provides temporary housing and other services for the houseless community in Portland. The lessons learned from these pandemic response initiatives are summarized here for student-run clinics, educators, and others interested in starting similar initiatives.